Towards a new design of ciphers to secure CPS: the role of control theory - Boukerrou, Hamid; Millerioux, Gilles; Minier, Marine (2022 26th International Conference on System Theory, Control and Computing (ICSTCC), 2022)
Among several solutions to face the unprecedented increase of attacks towards Cyber Physical Systems, encryption plays a central role. In the form of a Proof of Concept, this contribution gives a new methodology for designing self-synchronizing automata, having in mind their use in symmetric cryptography, namely the Self-Synchronizing Stream Ciphers. The contribution of the paper is to recast the design as control theoretical issues. It calls for a graph-based approach and results borrowed from control theory and dynamical systems, in particular LPV systems. The design leads to not necessarily T -functions as state transition functions of the automata involved in the ciphering and deciphering sides. It is a consideration that is important for the sake of security. Another asset of the approach is that the resulting ciphers admit possibly vectorial inputs to enhance the throughput.